1996
DOI: 10.1007/s0021663540483
|View full text |Cite
|
Sign up to set email alerts
|

Contaminant migration from food packaging laminates used for heat and eat meals

Abstract: EU legislation requires that components from food contact plastics should not migrate significantly into the food. The nature and extent of species migrating from laminated materials used for packaging 'heat and eat' meals have been investigated. Selected target analytes included additives incorporated into the polyolefin, e.g. the Irganox and Irgafos antioxidants, the diisocyanate and polyol residues from the adhesive and oligomeric material from the nylon. The results identified a wide range of migrants aris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 8 publications
0
16
0
1
Order By: Relevance
“…from flexible plastic films into food simulants (Lawson et al 1996(Lawson et al , 1999Brede et al 2003). Azo-colours can be used in printing inks for plastic, paper and board (Brede and Skjevrak 2004;Skjevrak et al 2005), and are also used as food additives, where both free and bound forms of PAAs have been characterized (Voyksner et al 1993;Lancaster and Lawrence 1999).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…from flexible plastic films into food simulants (Lawson et al 1996(Lawson et al , 1999Brede et al 2003). Azo-colours can be used in printing inks for plastic, paper and board (Brede and Skjevrak 2004;Skjevrak et al 2005), and are also used as food additives, where both free and bound forms of PAAs have been characterized (Voyksner et al 1993;Lancaster and Lawrence 1999).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Nevertheless, chemical substances can migrate from these articles to the food, and thereby contribute to food contamination. Another example of PAAs occurrence in food packaging and their migration from polyamide utensils into foodstuffs [3,4,5] may be due to remaining residues present from the colouring process (using azo-dyes) and co-monomer addition [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…All have identified ε-caprolactam as a principal migrant when Nylon 6 plastic materials have been used to seal, store or cook commodities (Bradley et al, 2004). Due to high cooking temperatures, monomers of Nylon and other constituents of the plastic packaging have been found to migrate to water or the packaged food, and the duration of heating has been positively correlated with ε-caprolactam migration (Gramshaw et al, 1998;Lawson et al, 1996;Sarbach et al, 1996). Results also indicate that solvent type and heating method can affect ε-caprolactam migration.…”
Section: Studies/researchmentioning
confidence: 97%
“…It has been common to test bags or pouches for plastics migration directly into foodstuffs or the aqueous solutions surrounding the foods. It was found that heat caused the migration of plastic components into both the food and surrounding solution (Gramshaw et al, 1998;Lawson et al, 1996;Sarbach et al, 1996).…”
Section: Studies/researchmentioning
confidence: 99%
See 1 more Smart Citation